Health Care Professionals’ Pain Narratives in Hospitalized Children’S Medical Records. Part 2: Structure and Content - Judy Rashotte; Denise Harrison; Geraldine Coburn; Janet Yamada; Bonnie J Stevens; the CIHR Team in Children’s Pain (Pain Research and Management)
BACKGROUND: Although clinical narratives – described as free-text notations – have been noted to be a source of patient information, no studies have examined the composition of pain narratives in hospitalized children’s medical records.